Potential benefits of digital fabrication for complex structures: Environmental assessment of a robotically fabricated concrete wall. (15th June 2017) - Agustí-Juan, Isolda; Müller, Florian; Hack, Norman; Wangler, Timothy; Habert, Guillaume
Abstract: Digital fabrication represents innovative, computer-controlled processes and technologies with the potential to expand the boundaries of conventional construction. Their use in construction is currently restricted to complex and iconic structures, but the growth potential is large. This paper aims to investigate the environmental opportunities of digital fabrication methods, particularly when applied to complex concrete geometries. A case study of a novel robotic additive process that is applied to a wall structure is evaluated with the Life Cycle Assessment (LCA) method. The results of the assessment demonstrate that digital fabrication provides environmental benefits when applied to complex structures. The results also confirm that additional complexity is achieved through digital fabrication without additional environmental costs. This study provides a quantitative argument to position digital fabrication at the beginning of a new era, which is often called the Digital Age in many other disciplines. Highlights: LCA comparison between robotic fabrication and conventional construction. Mesh Mould construction process analysed from an environmental point of view. Environmental benefits of digital fabrication when applied to complex structures. Justification of complexity from a sustainable perspective.